To the problem of Karachay-Balkar language’s functional development in KCR - M. R. Baychorov (Вестник Северо-Кавказского федерального университета, 2022)
The article offers a description of the functioning spheres for the Karachai-Balkar language in the Karachai-Circassian republic. There is a view on the issue of an efficient language policy as a factor maintaining the languages of the peoples residing in the KCR, in areas like science, culture, media, etc.